2019
DOI: 10.1073/pnas.1904636116
|View full text |Cite
|
Sign up to set email alerts
|

Integration of renewable deep eutectic solvents with engineered biomass to achieve a closed-loop biorefinery

Abstract: Despite the enormous potential shown by recent biorefineries, the current bioeconomy still encounters multifaceted challenges. To develop a sustainable biorefinery in the future, multidisciplinary research will be essential to tackle technical difficulties. Herein, we leveraged a known plant genetic engineering approach that results in aldehyde-rich lignin via down-regulation of cinnamyl alcohol dehydrogenase (CAD) and disruption of monolignol biosynthesis. We also report on renewable deep eutectic solvents (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 57 publications
1
66
0
Order By: Relevance
“…In order to ensure the stability and recyclability of the DES, several tests were performed which are described in full in the supporting Information. Previous studies have also investigated the recycling of DESs for lignin extraction and reported that this was achieved without significant changes in efficacy …”
Section: Resultsmentioning
confidence: 99%
“…In order to ensure the stability and recyclability of the DES, several tests were performed which are described in full in the supporting Information. Previous studies have also investigated the recycling of DESs for lignin extraction and reported that this was achieved without significant changes in efficacy …”
Section: Resultsmentioning
confidence: 99%
“…In CAD-deficient pine and poplar, higher quantity of these hydroxybenzaldehydes is released from biomass after alcohol-or alkaline-based extractions [109,110]. Furthermore, the effectiveness of hydrothermal treatments at releasing vanillin and syringaldehyde from biomass of CAD mutant plants was recently evidenced [111,112]. Development of environmentally friendly processes towards valorization of lignin streams generated in biorefineries has garnered interest, and it would be interesting to evaluate the yield of vanillin and syringaldehyde obtained from the depolymerization of lignins that derive from CAD mutants [113].…”
Section: Vanillin and Syringaldehydementioning
confidence: 99%
“…Recently, DESs synthesized from lignin-derivable phenolic compounds were found to be effective in lignin removal, and thus resulted in enhanced biomass saccharification efficacy . Also, renewable DESs prepared from phenolic aldehydes (e.g., vanillin and 4-hydroxybenzaldehyde) with choline chloride (ChCl), integrated with the use of low-recalcitrant engineered biomass via down-regulation of cinnamyl alcohol dehydrogenase (CAD), demonstrated the potential of developing a closed-loop biorefinery process (Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%